Lymphatic system regulation of anti-cancer immunity and metastasis - Lei, Pin-Ji; Fraser, Cameron; Jones, Dennis; Ubellacker, Jessalyn M.; Padera, Timothy P. (Frontiers in Immunology, 2024)
Cancer dissemination to lymph nodes (LN) is associated with a worse prognosis, increased incidence of distant metastases and reduced response to therapy. The LN microenvironment puts selective pressure on cancer cells, creating cells that can survive in LN as well as providing survival advantages for distant metastatic spread. Additionally, the presence of cancer cells leads to an immunosuppressive LN microenvironment, favoring the evasion of anti-cancer immune surveillance. However, recent studies have also characterized previously unrecognized roles for tumor-draining lymph nodes (TDLNs) in cancer immunotherapy response, including acting as a reservoir for pre-exhausted CD8+ T cells and stem-like CD8+ T cells. In this review, we will discuss the spread of cancer cells through the lymphatic system, the roles of TDLNs in metastasis and anticancer immune responses, and the therapeutic opportunities and challenges in targeting LN metastasis.